DEKONSTRUKSI KEADILAN DALAM POLIGAMI: : Membaca Ulang Perlindungan Istri Pertama dalam dialektika Hukum Perkawinan di Indonesia. - Syaf, Moh. Najib (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2025)
Ostensibly characterized as among the most progressive in the Muslim world, Indonesia’s polygamy regulations—codified under Law No. 1/1974 and the Compilation of Islamic Law (KHI)—persistently fail to mitigate the socio-legal precarity of first wives due to systemic procedural circumvention. This research interrogates the functional failures in safeguarding the rights of first wives through the analytical lens of Maqasid al-Shari’ah (teleological legal reasoning). Utilizing a normative-juridical approach, the study delineates a state of "formalistic protectionism," wherein the mandated consent of the first wife is frequently compromised by structural coercion and patriarchal hegemony. The findings demonstrate that in the absence of quantifiable justice indicators and robust digital verification mechanisms, the statutory requirement of "equity" remains a mere legal fiction. The novelty of this research lies in its synthesis of Jasser Auda’s systems-based Maqasid theory with a proposed digitalized marriage registration ecosystem designed to eliminate the jurisdictional loopholes of unregistered (siri) polygamy. Ultimately, this study advocates for a paradigm shift in the procedural law of Religious Courts, mandating a transition toward substantive justice to align national family law with global Sustainable Development Goal (SDG) 5 mandates on gender equality